La realidad de los medios de masas - Luhmann, Niklas, 1927-1998.; Torres Nafarrate, Javier (Rubí, Barcelona : Anthropos, Editorial del Hombre ; México D.F. : Universidad Iberoamericana, 2007)
"In The Reality of the Mass Media, Luhmann extends his theory of social systems to an examination of the role of mass media in the constitution of social reality." "Luhmann argues that the system of mass media is a set of recursive, self-referential programs of communication, whose functions are not determined by the external values of truthfulness, objectivity, or knowledge, nor by specific social interests or political directives. Rather, he contends that the system of mass media is regulated by the internal code information/noninformation, which enables the system to select its information (news) from its own environment and to communicate this information in accordance with its own reflexive criteria."--From the English ed.
In memoriam / Javier Torres Nafarrate -- 1. La diferenciación como duplicación de la realidad -- 2. Autorreferencia y heterorreferencia -- 3. Codificación -- 4. Universalismo específico del sistema -- 5. Noticias y reportajes -- 6. Ricúpero -- 7. Publicidad -- 8. Entretenimiento -- 9. Unidad y acoplamiento estructural -- 10. Individuos -- 11. La construcción de la realidad -- 12. La realidad de la construcción -- 13. La función de los medios de comunicación para las masas -- 14. Lo público -- 15. Formación de esquemas -- 16. Cibernética de segundo orden como paradoja -- Índice de materias.
Translation of : Die Realität der Massenmedien. Opladen : Westdeutscher Verlag, 1995.
First published: Rubí, Barcelona : Anthropos Editorial, 2000.
Keywords: Mass media -- Social aspects; Mass media -- Audiences; Communication -- Social aspects; Electronic books